Black Coffee Shop Customer Satisfaction Based on Product Quality and Service - Razak, A; Amrusi, Amrusi; Husna, Asmaul; Musfiana, Musfiana; Mustofa, Achmad (Journal of Economics Education and Entrepreneurship, 2021)
This research was conducted with the aim of knowing the level of customer satisfaction at the Black Coffee Shop business in the city of Banda Aceh. This research was conducted using a quantitative approach with descriptive methods. The sampling technique was simple random sampling, where each sample was taken randomly without looking at the strata. By using the Slovin formula, the number of samples in this study was 80 consumers. Analysis of research data using multiple linear regression analysis model which is used to see the effect between product quality and service variables (independent variables) on customer satisfaction (dependent variable). The results of the partial calculation of the variable product quality and service quality have a positive and significant effect on customer satisfaction. Between product quality and service quality, the more dominant quality is product quality. The results of the calculation of the coefficient of determination show that the variables of product quality and service quality can explain the change in customer satisfaction by 62.9%, while the remaining 37.1% is influenced by other factors not discussed in this study.